Nutritional properties of wheat flour supplemented with modified tacca (Tacca involucrata) flour for production of healthy biscuits - Ojewumi, Emmanuel Omotayo (2023)
Proximate composition (g/100 g) of modified Tacca flour The proximate composition of the native and modified tacca flour is presented in Table 1. The moisture content of all the samples ranged from 7.34 to 10.14%; total ash from 1.19 to 2.59%; crude protein from 5.56 to 14.08%; crude fibre from 1.23 to 2.91%; and carbohydrate content from 68.86 to 82.10%. The energy values ranged from 347.69 to 381.06 kcal/ 100 g.